Childhood adherence to a potentially healthy and sustainable Nordic diet and later overweight: The Norwegian Mother, Father and Child Cohort Study (MoBa) - Neha Agnihotri; Nina Cecilie Øverby; Elling Bere; Andrew Keith Wills; Anne Lise Brantsæter; Elisabet Rudjord Hillesund (Wiley, 2021)
Abstract The New Nordic Diet (NND) is a potentially healthy and sustainable dietary pattern represented by locally available and traditionally consumed foods in the Northern countries. The diet has been commonly examined in adult populations, but less is known regarding its potential associations with overweight/obesity in children. We have previously developed child diet scores measuring compliance to the NND at child age 6 and 18 months and 3 and 7 years. In this study, we aimed to describe child and maternal characteristics and assess potential associations between the age‐specific diet scores and child overweight at 8 years. This study is based on the Norwegian Mother, Father and Child Cohort Study (MoBa), including 14,989 mother-child pairs and uses data from the Medical Birth Registry of Norway (MBRN). The scores measured NND compliance as a total score and categorized into low, medium and high NND compliance at each age point. Using logistic regression models, we investigated the association between each age‐specific score and the odds of overweight at 8 years. In crude analyses, adherence to the NND at 6 months was inversely associated with odds of overweight at 8 years in the continuous score (odds ratio = 0.95, 95% CI [0.91, 0.98]) and when comparing high versus low NND adherence (odds ratio = 0.81, 95% CI [0.70, 0.94]). The association was almost entirely attenuated in the adjusted models. In conclusion, child NND adherence up to 7 years of age was not associated with odds of overweight at 8 years in adjusted analyses.